Nachhaltig durch die Krise? Eine empirische Analyse ausgewählter nachhaltiger Aktienindizes vor dem Hintergrund der COVID-19 Pandemie - Franziska Assel; Manuela Ender; Tim Herberger (IU Internationale Hochschule, 2022)
– Sustainability is not only becoming more and more important at the political level; the product range of sustainable investments is also growing rapidly in the financial sector. The COVID-19 pandemic has shown how important sustainable business models can be to survive crises. Therefore, this study examines selected sustainable stock indices during the COVID-19 pandemic and discusses whether it is advisable for investors and issuers to invest in sustainable financial products. The research question of whether sustainable stock indices have developed more stably and performed better than conventional indices in the COVID-19 pandemic is discussed applying the methodology of an event study. For this purpose, 33 sustainable and conventional stock indices are analyzed against the background of four selected events within the pandemic. The focus is on the European area. The results of the empirical analysis show that all selected indices - whether sustainable or conventional -react with abnormal returns in light of the selected events. In particular, significant market movements could be detected up to ten days after the event. In a direct comparison, however, the sustainable stock market barometers perform better than the conventional stock indices. Sustainable indices with a best-in-class approach are on average 0.13 percentage points ahead of sustainable indices without this approach. Based on the results obtained, involvement in sustainable financial products is recommended to both investors and issuers.
Keywords: G14; G15; Q50; 650; Ereignisstudie; Event Study; Abnormale Renditen; Nachhaltigkeit; Sustainability; Aktienindizes; COVID19-Pandemie